Tahap Penggunaan Sistem Aplikasi Komputer SPDK Di Kalangan Kakitangan Jabatan Ukur Dan Pemetaan Malaysia - Hj. Mohammad Yunus, Yusof (2002)

(untitled)
The main objective of this study is to measure the level of CDMS (Cadastral Data Management System) computer usage among the employees of DSMM (Department of Survey and Mapping Malaysia) as well as to identify factors (individual and organizational) that are related to its level of usage. The variables examined were demographic characteristics (gender, age, academic level, occupational level and work section), individual factors (computer knowledge and skill, computer anxiety and attitude towards computer), and organizational factors (computer training, management support and social pressure). A total of 421 questionnaires were distributed to the respondents in 12 States DSMM. Statistical analysis techniques such as Pearson correlation test and Chi-Square test were used to test 11 hypotheses. The results revealed that the level of CDMS computer usage among respondents is moderate and more towards positive direction. In addition, the study also found that there is relationship between the level of CDMS computer usage and age, academic level, occupational level, work section, computer knowledge and skill, computer anxiety, attitude towards computer, computer training, management support, and social pressure. However, there is no relationship between the level of CDMS computer usage and gender. As a conclusion, the results from this study are consistent with previous findings.